Effectiveness of Gamified Cooperation and Competition in Blended Learning Environment for EFL Business Writing in TVET - Mohamed, Khalid A.; El-Naggar, Mohamad Elsayed; Alazab, Gehan Sedky (European Scientific Journal, ESJ, 2024)
This research investigated the effectiveness of gamified blended learning environments in fostering EFL writing skills among technical and vocational education and training (TVET) trainees in Saudi Arabia. It compared three distinct learning strategies achieved through gamification design in a blended delivery mode: gamified cooperation, gamified competition, and gamified cooperation-competition. Each strategy leveraged a specific category of gamification features that evoke different goal structure: cooperation, competition, or a combination of both. A quasi-experimental design with a pre-test and post-test was employed. Forty-five trainees were purposively selected and randomly assigned to three groups, each receiving instruction using a different gamified blended learning program for teaching business writing. The findings revealed significant improvement in English as a Foreign Language business writing skills for all three groups. However, a one-way ANOVA and post-hoc Tukey HSD test indicated that the gamified cooperation-competition strategy yielded the greatest improvement compared to the gamified cooperation and gamified competition strategies alone. This suggests that a combination of cooperative and competitive elements within a gamified blended learning environment might be the most effective approach for enhancing English as a Foreign Language business writing skills among Technical and Vocational Training and Education learners.